A scenario-based modelling for the long-term energy planning based on efficient energy Use, economic and environmental emission reduction on national scale: A case study Iran - Fatemeh Salmanpour; Hossein Yousefi; Mehdi Ehsan (Energy Conversion and Management: X)
While Renewable Energies (REs) are not cost-effective in Iran yet, making changes in the structure of the energy system under a long-term energy plan could offer a suitable solution for a more sustainable system. In this paper, energy planning conducted for the case study of Iran. The main goal of this study is to provide a practical solution that can reduce emissions and costs, in addition to meeting the demands of different sectors including electricity, household, transportation, and industry. In this regard, five scenarios designed and analyzed with a focus on the share of REs, the efficiency of power plants, and the capacity of combined cycle power plants. In this modeling, the share of Res including wind and solar in electricity production increased from 0.2 % to 3.3 %. The average efficiency of Iran’s power plants increased from 37 % to 40.5 %, and the share of combined cycle power plants of the total thermal power plants increased from 35 % to 50 % from 2016 to 2050. The results of the cost analysis showed that applying the integrated scenario of REs and combined cycles would be effective in the reduction of total annual cost, carbon dioxide (CO2) emissions, and fossil fuel consumption. The average saved cost by integrated scenario is about $8.7 billion over 30 years compared to the business as usual (BAU). Also, the reduction in fossil fuel consumption and CO2 emission is 294.74 TWh and 65 million tons of CO2, respectively.